2017
DOI: 10.1108/jec-12-2016-0046
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial intentions of university students: a case-based study

Abstract: Purpose This study aims to examine the entrepreneurial intentions of university students at the International University of Sarajevo. For this purpose, the entrepreneurial desires and entrepreneurial orientations of the students across several demographic variables were measured. These variables included prior entrepreneurial experience, student’s gender, faculty, year of study and attitude towards more courses on entrepreneurship. Nevertheless, the research also examined how business environment influences th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 43 publications
2
64
1
3
Order By: Relevance
“…(2017) showed there was no significant difference in the entrepreneurial intentions of male and female students as well as on their age group in Nigerian undergrad students. To contrast with these findings, Palalic, Ramadani, Dilovic, Dizdarevic and Ratten (2017) found that students with prior entrepreneurial experience scored higher in both the entrepreneurial desire and orientation than students without experience. The same happens with the gender where males have higher entrepreneurial desire and orientation.…”
Section: Analysis Of the Results And Discussioncontrasting
confidence: 54%
“…(2017) showed there was no significant difference in the entrepreneurial intentions of male and female students as well as on their age group in Nigerian undergrad students. To contrast with these findings, Palalic, Ramadani, Dilovic, Dizdarevic and Ratten (2017) found that students with prior entrepreneurial experience scored higher in both the entrepreneurial desire and orientation than students without experience. The same happens with the gender where males have higher entrepreneurial desire and orientation.…”
Section: Analysis Of the Results And Discussioncontrasting
confidence: 54%
“…In this sense, universities play an essential role (Gnyawali & Fogel 1994). Thus, increasing the quantity and quality of courses on entrepreneurship may lead to an improvement of those skills and could have a positive influence on students who had not previously thought of becoming entrepreneurs (Palalić et al 2017).  Drivers to responsible research.…”
Section: University Social Responsibility and Its Driversmentioning
confidence: 99%
“…Üniversite öğrencilerinin girişimcilik eğilimini belirlemek için yapılan çalışmalarda ise genellikle bölüm, demografik özellikler, mesleki idealler ve cinsiyet gibi faktörler ele alınmış ve karşılaştırmalar yapılmıştır (Autio vd., 2001;Avşar, 2007;Börü, 2006;Dal, 2017;Gültekin vd., 2016;Isada vd., 2015;İşcan ve Kaygın, 2011;Kerrick, 2008;Korkmaz, 2012;Miciuliene ve Kargyte, 2017;Palalić vd., 2017;Sesen, 2013;Yao vd., 2016;Yüzüak, 2010). Wang ve Wong (2004) tarafından Singapur'daki üniversite öğrencilerinin girişimcilik eğilimlerini belirlemeye yönelik yapılan çalışma sonucunda öğrencilerin yüksek girişimcilik eğilimine sahip olduğu fakat yetersiz işletme bilgisi ve risk algısının girişimde bulunmak için caydırıcı olduğu, cinsiyet, ailenin iş deneyimi ve eğitim seviyesinin girişimcilik eğilimini etkilediği ancak aile gelir durumunun, etnik kökenin ve yaşanılan şehrin girişimcilik eğilimine etkisi olmadığı belirlenmiştir.…”
Section: Li̇teratür İncelemesi̇unclassified